Molecular mapping of all-stage stripe rust resistance in Indian wheat (Triticum aestivum) cultivar ‘VL404’ - Baranwal, Deepak; Qureshi, Naeela; Forrest, Kerrie L.; Bariana, Harbans S.; Bansal, Urmil (Wiley, 2022)
Puccinia striiformis f. sp. tritici (Pst), the causal agent of stripe rust of wheat, is a highly evolving fungal pathogen and several widely deployed stripe rust resistance genes have been overcome worldwide often through single step increase in virulence. Development of stripe rust resistant cultivars depends on the availability of widely effective sources of resistance. An Indian wheat cultivar ‘VL404’ exhibited high level of resistance against Australian Pst pathotypes. ‘VL404’ was crossed with a susceptible genotype Avocet ‘S’ (AvS) and an F6 recombinant inbred line (RIL) population was developed. The VL404/AvS RIL population was evaluated at the seedling stage against three Pst pathotypes differing in their virulence profiles. Monogenic segregation for stripe rust response variation was observed in this population and the resistance locus was tentatively named YrVL. Incorporation of stripe rust data into the VL404/AvS genetic map constructed using 40K Wheat-Barley Illumina XT single-nucleotide polymorphism (SNP) array placed YrVL in the long arm of chromosome 2B in the 769.1–779.3 Mb region of the Chinese Spring physical map. YrVL was aligned with the previously reported genes in chromosome 2BL (Yr43, Yr72 and YrAW12) using Pretzel, and it was placed distal to all these genes. Hence, YrVL appears to represent a new resistance locus.